Post-flowering photoperiod and radiation interaction in soybean yield determination: Direct and indirect photoperiodic effects - Nico, Magalí (2015)
Soybean (Glycine max (L.) Merrill) exposure to long days during the post-flowering phase increases total biomass, nodes, pods and seeds per plant, and also the post-flowering duration, increasing the radiation offer. This work aims to identify the main mechanisms responsible for yield increases in response to long days, separating direct photoperiodic effects on yield determination, from the indirect effect associated with changes in cumulative radiation when the crop cycle is modified by photoperiod. Two field experiments were conducted with an indeterminate soybean cultivar. A factorial combination of two radiation levels (unshaded and shaded), and two or three photoperiod regimes (control, extended 1.5 and 3 h) was imposed from flowering to maturity. Yield tended to be reduced by shade and increased by extended photoperiod mainly through their effects on nodes per m2, and thereby affecting pods and seeds per m2. Photoperiod extension increased node number due to both increased cumulative radiation (indirect effect) and delayed reproductive development (direct effect). As a result, more pods were established per unit of cumulative radiation under extended photoperiod. The results suggest that photoperiod extension enhanced yield radiation use efficiency due to the alleviation of intra-nodal interferences. The direct post-flowering photoperiodic effect on node number and the resultant effects on pod and seed number, provide evidence of direct photoperiodic effects on soybean yield determination.